Lead-lithium battery and preparation method thereof
By using dual-conducting lithium material and lead powder in lead lithium batteries, a high-conductivity large-pore structure is formed, which solves the problems of poor energy storage capacity and low conductivity, and improves the charging and discharge speed and life of the battery , improving the cycling experience of electric vehicles.
Patent Information
- Application Number
- CN202411106863.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-13
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-08-13
AI Technical Summary
The existing lead-lithium batteries have poor energy storage capacity, low conductivity, and slow charging and discharging speed, resulting in poor electric bike riding experience and short battery life.
The double-conducting lithium material and lead powder are mixed with specific pH and temperature conditions to prepare the positive electrode and negative electrode paste, and a high-conductivity large pore size structure is formed through the curing and assembly process to improve the surface area and conductivity of the electrode material.
It significantly improves the energy storage capacity and conductivity of lead-lithium batteries, increases the charging and discharging speed, extends the battery life, and optimizes the riding experience of electric vehicles.
Smart Images

Figure CN118630339B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery preparation, and in particular to a lead-lithium battery and a preparation method thereof. Background Art
[0002] The lead-acid batteries of electric vehicles have gone through two stages: the externalization of lead, antimony and cadmium into batteries and the internalization of lead, calcium, tin and aluminum into batteries, which has greatly promoted the development of new energy electric vehicles in my country. However, some problems have also been exposed, such as the conductive path of the battery is lead metal, which is manifested as poor energy storage capacity, low conductivity, poor conductivity, slow charging and discharging speed, thus reducing the service life of the battery and resulting in a poor riding experience of electric vehicles, which needs to be solved urgently. Summary of the invention
[0003] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a lead-lithium battery and a preparation method thereof, aiming to solve the problems of poor energy storage capacity, low conductivity, poor electrical conductivity, slow charging and discharging speed, and short service life of the current battery.
[0004] In order to achieve the above object, the present invention adopts the following technical solutions:
[0005] In a first aspect, a method for preparing a lead-lithium battery comprises the following steps:
[0006] Putting the lead block into a ball mill to prepare lead powder;
[0007] preparing positive electrode lead paste and negative electrode lead paste;
[0008] When preparing the positive lead paste and the negative lead paste, add the dual-conductive crystal lithium material thereto, specifically: mix an appropriate amount of electrolyte containing the dual-conductive crystal lithium material with formula water, adjust the pH value to 2-3, heat it to 80°C, quickly add it to the paste pot and stir it with the lead powder, maintain the temperature at 75-80°C, stir for 15 minutes, slowly add the remaining formula amount of the dual-conductive crystal lithium material electrolyte, continue stirring for 10-15 minutes after the dual-conductive crystal lithium material electrolyte is added, and obtain the corresponding positive lead paste and negative lead paste;
[0009] preparing positive electrode grids and negative electrode grids;
[0010] After setting the coating speed of the coating machine, the positive electrode lead paste is coated on the positive electrode grid, and the negative electrode lead paste is coated on the negative electrode grid;
[0011] 1.250ɡ / cm3 dilute sulfuric acid and 1% anhydrous sodium sulfate are prepared into a 1.260ɡ / cm3 electrolyte base solution, and then a specified amount of double-conductive crystal lithium material is added to the electrolyte base solution, and stirred at a speed of 1400r / min for 68min to obtain a double-conductive crystal lithium electrolyte;
[0012] The positive electrode grid coated with positive electrode lead paste and the negative electrode grid coated with negative electrode lead paste are subjected to acid showering operation, and then surface drying treatment is performed to obtain an intermediate positive electrode plate and an intermediate negative electrode plate;
[0013] The temperature, relative humidity and curing time are set during curing, and then the middle positive plate and the middle negative plate are sent to the curing room for curing;
[0014] Slicing and grinding the cured intermediate positive electrode plate and the cured intermediate negative electrode plate to obtain finished positive electrode plates and finished negative electrode plates;
[0015] Assembling the finished positive electrode plate and the finished negative electrode plate, and then injecting the double-conductive crystal lithium electrolyte to obtain an intermediate lead-lithium battery;
[0016] The intermediate lead-lithium battery is formed by adopting an internal formation process to obtain a lead-lithium battery.
[0017] Preferably, the preparation of the positive electrode lead paste specifically comprises the following steps:
[0018] Add corresponding materials into the lead powder measuring bucket, sulfuric acid measuring bucket and pure water measuring bucket according to the formula dosage;
[0019] Add measured lead powder into the paste pot;
[0020] Pour the specified number of bags of positive electrode dry powder additives approved by weight into the paste pot, and start the paste machine for dry mixing for 8 minutes;
[0021] After dry mixing is completed, add the formulated amount of pure water to the paste pot within 1 to 2 minutes without stopping the machine, and stir for another 8 minutes. During the stirring process after adding water, keep the lead paste temperature no higher than 50°C;
[0022] Evenly add the measured dilute sulfuric acid into the paste pot while adding water and stirring, and add it within 14-18 minutes. Turn on the circulating cooling water for cooling while adding the dilute sulfuric acid. When 1 / 3 of the dilute sulfuric acid is added, turn on the dust removal equipment to cool down until the stirring is finished to obtain the positive electrode lead paste.
[0023] Preferably, the preparation of the negative electrode lead paste specifically comprises the following steps:
[0024] Add corresponding materials into the lead powder measuring bucket, sulfuric acid measuring bucket and pure water measuring bucket according to the formula dosage;
[0025] Add measured lead powder into the paste pot;
[0026] Pour the specified number of bags of negative electrode dry powder additives approved by weight into the paste pot, and start the paste machine for dry mixing for 8 minutes;
[0027] After dry mixing is completed, add the formulated amount of pure water to the paste pot within 1 to 2 minutes without stopping the machine, and stir for another 5 minutes. During the stirring process after adding water, keep the lead paste temperature no higher than 50°C;
[0028] Evenly add the measured amount of dilute sulfuric acid into the paste pot while adding water and stirring, and add it within 13-17 minutes. Turn on the circulating cooling water for cooling while adding the dilute sulfuric acid. When 1 / 3 of the dilute sulfuric acid is added, turn on the dust removal equipment to cool down until the stirring is finished to obtain the negative electrode lead paste.
[0029] Preferably, preparing the positive electrode grid comprises the following steps:
[0030] The temperature range of the lead melting furnace is set to 505°C-535°C, and then the material for preparing the positive electrode grid is put into the lead melting furnace to melt;
[0031] When the temperature in the lead melting furnace reaches 480°C, turn on the mold heating knob and set the temperature range of the die mouth to 125-155°C and the temperature range of the mold bottom to 135-165°C;
[0032] Turn on the lead spoon heating knob and set the heating temperature range to 505℃-535℃;
[0033] Spray release agent evenly on the movable mold and fixed mold;
[0034] The molten lead in the lead spoon is poured into the mold, and then the mold is removed to obtain the positive electrode grid.
[0035] Preferably, preparing the negative electrode grid comprises the following steps:
[0036] The temperature range of the lead melting furnace is set to 505°C-535°C, and then the material for preparing the negative electrode grid is put into the lead melting furnace to melt;
[0037] When the temperature in the lead melting furnace reaches 490°C, turn on the mold heating knob and set the temperature range of the die mouth to 125-155°C and the temperature range of the mold bottom to 135-165°C;
[0038] Turn on the lead spoon heating knob and set the heating temperature range to 535℃-565℃;
[0039] Spray release agent evenly on the movable mold and fixed mold;
[0040] The molten lead in the lead spoon is poured into the mold, and then the mold is removed to obtain the negative electrode grid.
[0041] Preferably, the coating speed of the positive electrode grid is 120 pieces / min, and the coating speed of the negative electrode grid is 130 pieces / min.
[0042] Preferably, in the curing operation, the temperature of the first curing stage is 65°C-75°C, the relative humidity is greater than or equal to 99%, and the curing time is 20 hours; the temperature of the second curing stage is 55°C-65°C, the relative humidity is greater than or equal to 95%, and the curing time is 8 hours.
[0043] Preferably, the density of acid addition in the internal formation process is 1.255 g / ml; a two-stage formation current is adopted, the first stage current is 0.07C, the time is 1 hour, the second stage current is 0.15C, the time is 17h, and the formation capacity is 2.5 times the theoretical capacity.
[0044] In a second aspect, a lead-lithium battery is prepared using the above-mentioned preparation method.
[0045] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0046] Adding dual-conductive crystal lithium material and controlling the pH value during the formation of the paste are conducive to the smooth formation of more 4BS. The addition of dual-conductive crystal lithium material changes the plate group. The larger the surface area of the electrode material, the more ions adsorbed, the stronger the energy storage capacity, the reasonable pore size distribution and the high conductivity, the good conductivity of the electrode material, the ions adsorbed on the electrode surface can be quickly transmitted to the electrode, the charging and discharging speed becomes faster, and the charging and discharging current increases. After formation, the lead-lithium battery in the embodiment obtains a large number of large-sized 4BS crystals and a large-pore lead paste structure, which can be used as a channel for electrolyte sulfuric acid, improves the utilization rate of active materials and large-current discharge performance, greatly extends the battery life, and thus optimizes and enhances the riding experience of the electric vehicle. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0048] Figure 1 A flow chart of a method for preparing a lead-lithium battery is shown.
[0049] Figure 2 The SEM morphology of 4BS grains at the initial stage of formation is shown.
[0050] Figure 3 The SEM morphology of β-PbO2 in the middle stage of formation is shown.
[0051] Figure 4 The SEM morphology of β-PbO2 at the later stage of formation is shown.
[0052] Figure 5 The SEM morphology of the lead-lithium battery plate containing 4BS prepared in the example is shown.
[0053] Figure 6 The SEM morphology of the comparative lead-lithium battery is shown. DETAILED DESCRIPTION
[0054] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0055] Reference Figures 1 to 6 The present invention further describes a lead-lithium battery and a method for preparing the same.
[0056] Embodiment, electrolytic lead is selected as raw material, and the electrolytic lead is put into a ball mill to prepare lead powder;
[0057] 1.250ɡ / cm3 dilute sulfuric acid and 1% anhydrous sodium sulfate are prepared into a 1.260ɡ / cm3 electrolyte base solution, and then a specified amount of double-conductive crystal lithium material is added to the electrolyte base solution, and stirred at a speed of 1400r / min for 68min to obtain a double-conductive crystal lithium electrolyte;
[0058] Add corresponding materials into the lead powder measuring bucket, sulfuric acid measuring bucket and pure water measuring bucket according to the formula dosage;
[0059] Add measured lead powder to the paste pot; disperse and pour the specified number of bags of positive electrode special dry powder additives that have been approved by weight into the paste pot, start the paste machine and dry mix for 8 minutes; after the dry mixing is completed, add the formulated amount of pure water to the paste pot within 1 to 2 minutes without stopping the machine, and stir for another 8 minutes. During the stirring process after adding water, keep the lead paste temperature no higher than 50°C; while adding water and stirring, slowly and evenly add the measured 1.4g / cm3 of dilute sulfuric acid to the paste pot until the pH value is adjusted to about 2, and then heat the solution temperature of pH 2 to 75°C, and add 1.4g / cm3 of dilute sulfuric acid during the process. During the process, a proper amount of electrolyte containing dual-conductive crystal lithium material is mixed with formula water, adjusted to a pH value of 2-3, and after heating to 80°C, it is quickly added to the paste pot and stirred with lead powder, and the temperature is maintained at 75-80°C. After stirring for 15 minutes, the remaining formula amount of dual-conductive crystal lithium material electrolyte is slowly added. After the addition of the dual-conductive crystal lithium material electrolyte is completed, stirring is continued for 10-15 minutes, and 1.4g / cm3 of dilute sulfuric acid is added within 14-18 minutes. When adding dilute sulfuric acid, the circulating cooling water is turned on for cooling. When 1 / 3 of the dilute sulfuric acid is added, the dust removal equipment is turned on to cool down until the stirring is completed to obtain the positive lead paste;
[0060] Add measured lead powder to the paste pot; disperse and pour the specified number of bags of positive electrode special dry powder additives that have been approved by weight into the paste pot, start the paste machine and dry mix for 8 minutes; after the dry mixing is completed, add the formulated amount of pure water to the paste pot within 1 to 2 minutes without stopping the machine, and stir for another 5 minutes. During the stirring process after adding water, keep the lead paste temperature no higher than 50°C; while adding water and stirring, slowly and evenly add measured 1.4g / cm3 of dilute sulfuric acid to the paste pot until the pH value is adjusted to about 2, and then heat the solution temperature of pH 2 to 75°C, and add 1.4g / cm3 of dilute sulfuric acid during the process. During the process, a proper amount of electrolyte containing dual-conductive crystal lithium material is mixed with formula water, adjusted to a pH value of 2-3, and after heating to 80°C, it is quickly added to the paste pot and stirred with lead powder, and the temperature is maintained at 75-80°C. After stirring for 15 minutes, the remaining formula amount of dual-conductive crystal lithium material electrolyte is slowly added. After the addition of the dual-conductive crystal lithium material electrolyte is completed, stirring is continued for 10-15 minutes, and 1.4g / cm3 of dilute sulfuric acid is added within 13-17 minutes. When adding dilute sulfuric acid, the circulating cooling water is turned on for cooling. When 1 / 3 of the dilute sulfuric acid is added, the dust removal equipment is turned on to cool down until the stirring is completed to obtain the negative electrode lead paste;
[0061] The temperature range of the lead melting furnace is set to 505°C-535°C, and then the material for preparing the positive electrode grid is put into the lead melting furnace to melt; when the temperature in the lead melting furnace reaches 480°C, the mold heating knob is turned on, and the temperature range of the mold mouth is set to 125-155°C, and the temperature range of the mold bottom is set to 135-165°C; the lead spoon heating knob is turned on, and the heating temperature range is set to 505°C-535°C; the mold release agent is evenly sprayed on the movable mold and the fixed mold; the molten lead in the lead spoon is poured into the mold, and then the mold is demolded to obtain the positive electrode grid;
[0062] The temperature range of the lead melting furnace is set to 505°C-535°C, and then the material for preparing the negative electrode grid is put into the lead melting furnace to melt; when the temperature in the lead melting furnace reaches 490°C, the mold heating knob is turned on, and the temperature range of the mold mouth is set to 125-155°C, and the temperature range of the mold bottom is set to 135-165°C; the lead spoon heating knob is turned on, and the heating temperature range is set to 535°C-565°C; the mold release agent is evenly sprayed on the movable mold and the fixed mold; the molten lead in the lead spoon is poured into the mold, and then the mold is demolded to obtain the negative electrode grid;
[0063] The coating speed of the coating machine for the positive grid is set to 120 pieces / min, and the coating speed for the negative grid is set to 130 pieces / min, and the positive lead paste is coated on the positive grid, and the negative lead paste is coated on the negative grid;
[0064] The positive electrode grid coated with positive electrode lead paste and the negative electrode grid coated with negative electrode lead paste are subjected to acid showering operation, and then surface drying treatment is performed to obtain an intermediate positive electrode plate and an intermediate negative electrode plate;
[0065] The temperature of the first stage of curing is set to 65°C-75°C, the relative humidity is greater than or equal to 99%, and the curing time is 20 hours; the temperature of the second stage of curing is set to 55°C-65°C, the relative humidity is greater than or equal to 95%, and the curing time is 8 hours, and then the intermediate positive plate and the intermediate negative plate are sent to the curing room for curing treatment;
[0066] Slicing and grinding the cured intermediate positive electrode plate and the cured intermediate negative electrode plate to obtain finished positive electrode plates and finished negative electrode plates;
[0067] Assembling the finished positive electrode plate and the finished negative electrode plate, and then injecting the double-conductive crystal lithium electrolyte to obtain an intermediate lead-lithium battery;
[0068] The lead-lithium battery is formed by an internal formation process, and the lead-lithium battery is obtained. The internal formation process is specifically that the acid density is 1.255g / ml; a two-stage formation current is adopted, the first stage current is 0.07C, the time is 1 hour, the second stage current is 0.15C, the time is 17h, and the formation capacity is 2.5 times of the theoretical capacity;
[0069] It should be noted that in the initial stage of formation: in the alkaline region, 4BS grains start from the surface through "metasomal reaction" to generate aggregated α-PbO2 based on nanocrystalline primary particles, and retain the rod-like structural characteristics of 4BS, so that the cured plate has shape memory properties after formation;
[0070] Mid-stage: Substitution reaction continues to occur inside the 4BS crystal to form a thicker α-PbO2 core, while needle-shaped or rod-shaped primary particles β-PbO2 are generated on the surface of the α-PbO2 core through dissolution and reprecipitation in the gradually increasing acidic environment on the surface, forming a "core-shell" structure.
[0071] Late stage: The residual lead sulfate crystals dissolve and reprecipitate to form β-PbO2, which is continuously deposited, making the β-PbO2 coarser and growing from rods to blocks.
[0072] In a comparative example, electrolytic lead was selected as a raw material, and the electrolytic lead was put into a ball mill to prepare lead powder;
[0073] Add corresponding materials into the lead powder measuring bucket, sulfuric acid measuring bucket and pure water measuring bucket according to the formula dosage;
[0074] Add the measured lead powder into the paste pot, and then add the formulated amount of pure water into the paste pot without stopping the machine and within 1 to 2 minutes, and stir for 15 minutes. During the stirring process after adding water, keep the lead paste temperature no more than 50°C; slowly and evenly add the measured 1.4g / cm3 of dilute sulfuric acid into the paste pot while adding water and stirring, until the pH value is adjusted to about 2, and then heat the solution temperature of pH 2 to 75°C. During the process of adding 1.4g / cm3 of dilute sulfuric acid, disperse and pour the specified number of bags of positive electrode special dry powder additives that have been weight-approved into the paste pot, maintain the temperature at 75-80°C, stir for 10 minutes, and add 1.4g / cm3 of dilute sulfuric acid within 14-18 minutes. Add the dilute sulfuric acid and turn on the circulating cooling water for cooling. When 1 / 3 of the dilute sulfuric acid is added, turn on the dust removal equipment to cool down until the stirring is completed to obtain the positive electrode lead paste;
[0075] Add the measured lead powder into the paste pot, and then add the formulated amount of pure water into the paste pot without stopping the machine and within 1 to 2 minutes, and stir for 15 minutes. During the stirring process after adding water, keep the lead paste temperature no higher than 50°C; slowly and evenly add the measured 1.4g / cm3 of dilute sulfuric acid into the paste pot while adding water and stirring, until the pH value is adjusted to about 2, and then heat the solution temperature of pH 2 to 75°C. During the process of adding 1.4g / cm3 of dilute sulfuric acid, disperse and pour the specified number of bags of positive electrode special dry powder additives that have been weight-approved into the paste pot, maintain the temperature at 75-80°C, stir for 10 minutes, and add 1.4g / cm3 of dilute sulfuric acid within 13-17 minutes. Add the dilute sulfuric acid and turn on the circulating cooling water for cooling. When 1 / 3 of the dilute sulfuric acid is added, turn on the dust removal equipment to cool down until the stirring is completed to obtain the negative electrode lead paste;
[0076] The temperature range of the lead melting furnace is set to 505°C-535°C, and then the material for preparing the positive electrode grid is put into the lead melting furnace to melt; when the temperature in the lead melting furnace reaches 480°C, the mold heating knob is turned on, and the temperature range of the mold mouth is set to 125-155°C, and the temperature range of the mold bottom is set to 135-165°C; the lead spoon heating knob is turned on, and the heating temperature range is set to 505°C-535°C; the mold release agent is evenly sprayed on the movable mold and the fixed mold; the molten lead in the lead spoon is poured into the mold, and then the mold is demolded to obtain the positive electrode grid;
[0077] The temperature range of the lead melting furnace is set to 505°C-535°C, and then the material for preparing the negative electrode grid is put into the lead melting furnace to melt; when the temperature in the lead melting furnace reaches 490°C, the mold heating knob is turned on, and the temperature range of the mold mouth is set to 125-155°C, and the temperature range of the mold bottom is set to 135-165°C; the lead spoon heating knob is turned on, and the heating temperature range is set to 535°C-565°C; the mold release agent is evenly sprayed on the movable mold and the fixed mold; the molten lead in the lead spoon is poured into the mold, and then the mold is demolded to obtain the negative electrode grid;
[0078] The coating speed of the coating machine for the positive grid is set to 120 pieces / min, and the coating speed for the negative grid is set to 130 pieces / min, and the positive lead paste is coated on the positive grid, and the negative lead paste is coated on the negative grid;
[0079] The positive electrode grid coated with positive electrode lead paste and the negative electrode grid coated with negative electrode lead paste are subjected to acid showering operation, and then surface drying treatment is performed to obtain an intermediate positive electrode plate and an intermediate negative electrode plate;
[0080] The temperature of the first stage of curing is set to 65°C-75°C, the relative humidity is greater than or equal to 99%, and the curing time is 20 hours; the temperature of the second stage of curing is set to 55°C-65°C, the relative humidity is greater than or equal to 95%, and the curing time is 8 hours, and then the intermediate positive plate and the intermediate negative plate are sent to the curing room for curing treatment;
[0081] Slicing and grinding the cured intermediate positive electrode plate and the cured intermediate negative electrode plate to obtain finished positive electrode plates and finished negative electrode plates;
[0082] Assembling the finished positive electrode plate and the finished negative electrode plate to obtain an intermediate lead-lithium battery;
[0083] The intermediate lead-lithium battery was formed by an internal formation process to obtain a control lead-lithium battery. The specific internal formation process is that the acid density is 1.255g / ml; a two-stage formation current is adopted, the first stage current is 0.07C, the time is 1 hour, the second stage current is 0.15C, the time is 17h, and the formation capacity is 2.5 times of the theoretical capacity.
[0084] The lead-lithium battery prepared in the embodiment and the control lead-lithium battery prepared in the comparative example were discharged three times for 3 hours, with a current of 33.3A and a termination voltage of 10.5vV. The normal charging method was: after charging to 14.8V at 15A, change to 10A and continue charging until the voltage changes by no more than 0.05V within 2h.
[0085] The test results are shown in Table 1:
[0086] Table 1 is a comparison table of discharge time of lead-lithium batteries of the embodiment and lead-lithium batteries of the reference example under different discharge times:
[0087]
[0088] It can be found from Table 1 that the first discharge time of the lead-lithium battery of the embodiment after formation is longer than that of the lead-lithium battery of the control, and the discharge time of the lead-lithium battery of the embodiment is 10 minutes longer than that of the lead-lithium battery of the control during the third discharge.
[0089] High rate discharge test
[0090] The fully charged lead-lithium battery of the embodiment and the fully charged lead-lithium battery of the control were subjected to a high rate discharge test with a test current of 100A. The test results showed that the discharge time of the lead-lithium battery of the embodiment was 49 minutes, and the discharge time of the lead-lithium battery of the control was 42 minutes.
[0091] Cyclic durability test
[0092] The lead-lithium battery of the embodiment and the control lead-lithium battery with a discharge capacity higher than 100% of the rated capacity were subjected to a cycle life test according to GB / T32620-2016 (Technical Conditions for Lead-Acid Batteries for Road Vehicles).
[0093] Discharge: 50A discharge for 1.6h; constant voltage 2.45v.
[0094] Charging: 50A charging for 4 hours;
[0095] One cycle is 4 hours of charging and 1.6 hours of discharging, and the test temperature is kept at 25°C. A 3-hour discharge test is performed every 49 cycles. When the 3-hour discharge capacity is detected to be less than 80% of the rated capacity, the battery is considered to be failed, and this round of cycles is not counted in the number of cycles.
[0096] The test results show that the cycle life of the lead-lithium battery of the embodiment is 490 times, and the cycle life of the lead-lithium battery of the control is 395 times.
[0097] The lead paste in the lead-lithium battery of the embodiment after formation was observed by scanning electron microscope (SEM). Figure 1 From the figure, it can be found that under normal formation, a large number of large 4BS crystals are still found. The lead paste in the control lead-lithium battery after formation was observed by scanning electron microscope (SEM). Figure 2 From the figure, it can be found that there is a large amount of tribasic lead sulfate in the lead paste, and no 4BS crystals are found. The 4BS crystals are obtained under the condition of normal formation in the example;
[0098] It can be seen that adding dual-conductive crystal lithium material and controlling the pH value during the formation of paste are conducive to the smooth formation of more 4BS. The addition of dual-conductive crystal lithium material changes the plate group. The larger the surface area of the electrode material, the more ions adsorbed, the stronger the energy storage capacity, the reasonable pore size distribution and the high conductivity, the good conductivity of the electrode material, the ions adsorbed on the electrode surface can be quickly transmitted to the electrode, the charging and discharging speed becomes faster, and the charging and discharging current increases. After formation, the lead-lithium battery in the embodiment obtains a large number of large-sized 4BS crystals and a large-pore lead paste structure, which can be used as a channel for electrolyte sulfuric acid, improves the utilization rate of active materials and large current discharge performance, and greatly extends the battery life.
[0099] The above description of the embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a lead-lithium battery, characterized in that: The steps include: Putting the lead block into a ball mill to prepare lead powder; preparing positive electrode lead paste and negative electrode lead paste; When preparing the positive lead paste and the negative lead paste, add the dual-conductive crystal lithium material thereto, specifically: mix an appropriate amount of electrolyte containing the dual-conductive crystal lithium material with formula water, adjust the pH value to 2-3, heat it to 80°C, quickly add it to the paste pot and stir it with the lead powder, maintain the temperature at 75-80°C, stir for 15 minutes, slowly add the remaining formula amount of the dual-conductive crystal lithium material electrolyte, continue stirring for 10-15 minutes after the dual-conductive crystal lithium material electrolyte is added, and obtain the corresponding positive lead paste and negative lead paste; preparing positive electrode grids and negative electrode grids; After setting the coating speed of the coating machine, the positive electrode lead paste is coated on the positive electrode grid, and the negative electrode lead paste is coated on the negative electrode grid; 1.250ɡ / cm3 dilute sulfuric acid and 1% anhydrous sodium sulfate are prepared into a 1.260ɡ / cm3 electrolyte base solution, and then a specified amount of double-conductive crystal lithium material is added to the electrolyte base solution, and stirred at a speed of 1400r / min for 68min to obtain a double-conductive crystal lithium electrolyte; The positive electrode grid coated with positive electrode lead paste and the negative electrode grid coated with negative electrode lead paste are subjected to acid showering operation, and then surface drying treatment is performed to obtain an intermediate positive electrode plate and an intermediate negative electrode plate; The temperature, relative humidity and curing time are set during curing, and then the middle positive plate and the middle negative plate are sent to the curing room for curing; Slicing and grinding the cured intermediate positive electrode plate and the cured intermediate negative electrode plate to obtain finished positive electrode plates and finished negative electrode plates; Assembling the finished positive electrode plate and the finished negative electrode plate, and then injecting the double-conductive crystal lithium electrolyte to obtain an intermediate lead-lithium battery; The intermediate lead-lithium battery is formed by adopting an internal formation process to obtain a lead-lithium battery.
2. The method for preparing a lead-lithium battery according to claim 1, characterized in that: The preparation of positive electrode lead paste specifically includes the following steps: Add corresponding materials into the lead powder measuring bucket, sulfuric acid measuring bucket and pure water measuring bucket according to the formula dosage; Add measured lead powder into the paste pot; Pour the specified number of bags of positive electrode dry powder additives approved by weight into the paste pot, and start the paste machine for dry mixing for 8 minutes; After dry mixing is completed, add the formulated amount of pure water to the paste pot within 1 to 2 minutes without stopping the machine, and stir for another 8 minutes. During the stirring process after adding water, keep the lead paste temperature no higher than 50°C; Evenly add the measured dilute sulfuric acid into the paste pot while adding water and stirring, and add it within 14-18 minutes. Turn on the circulating cooling water for cooling while adding the dilute sulfuric acid. When 1 / 3 of the dilute sulfuric acid is added, turn on the dust removal equipment to cool down until the stirring is finished to obtain the positive electrode lead paste.
3. The method for preparing a lead-lithium battery according to claim 2, characterized in that: The preparation of negative electrode lead paste specifically includes the following steps: Add corresponding materials into the lead powder measuring bucket, sulfuric acid measuring bucket and pure water measuring bucket according to the formula dosage; Add measured lead powder into the paste pot; Pour the specified number of bags of negative electrode dry powder additives approved by weight into the paste pot, and start the paste machine for dry mixing for 8 minutes; After dry mixing is completed, add the formulated amount of pure water to the paste pot within 1 to 2 minutes without stopping the machine, and stir for another 5 minutes. During the stirring process after adding water, keep the lead paste temperature no higher than 50°C; Evenly add the measured amount of dilute sulfuric acid into the paste pot while adding water and stirring, and add it within 13-17 minutes. Turn on the circulating cooling water for cooling while adding the dilute sulfuric acid. When 1 / 3 of the dilute sulfuric acid is added, turn on the dust removal equipment to cool down until the stirring is finished to obtain the negative electrode lead paste.
4. The method for preparing a lead-lithium battery according to claim 3, characterized in that: The preparation of the positive electrode grid includes the following steps: The temperature range of the lead melting furnace is set to 505°C-535°C, and then the material for preparing the positive electrode grid is put into the lead melting furnace to melt; When the temperature in the lead melting furnace reaches 480°C, turn on the mold heating knob and set the temperature range of the die mouth to 125-155°C and the temperature range of the mold bottom to 135-165°C; Turn on the lead spoon heating knob and set the heating temperature range to 505℃-535℃; Spray release agent evenly on the movable mold and fixed mold; The molten lead in the lead spoon is poured into the mold, and then the mold is removed to obtain the positive electrode grid.
5. The method for preparing a lead-lithium battery according to claim 4, characterized in that: The preparation of the negative electrode grid includes the following steps: The temperature range of the lead melting furnace is set to 505°C-535°C, and then the material for preparing the negative electrode grid is put into the lead melting furnace to melt; When the temperature in the lead melting furnace reaches 490°C, turn on the mold heating knob and set the temperature range of the die mouth to 125-155°C and the temperature range of the mold bottom to 135-165°C; Turn on the lead spoon heating knob and set the heating temperature range to 535℃-565℃; Spray release agent evenly on the movable mold and fixed mold; The molten lead in the lead spoon is poured into the mold, and then the mold is removed to obtain the negative electrode grid.
6. The method for preparing a lead-lithium battery according to claim 5, characterized in that: The coating speed of the positive electrode grid is 120 pieces / min, and the coating speed of the negative electrode grid is 130 pieces / min.
7. The method for preparing a lead-lithium battery according to claim 6, characterized in that: During the curing operation, the temperature of the first stage of curing is 65°C-75°C, the relative humidity is greater than or equal to 99%, and the curing time is 20 hours; the temperature of the second stage of curing is 55°C-65°C, the relative humidity is greater than or equal to 95%, and the curing time is 8 hours.
8. The method for preparing a lead-lithium battery according to claim 7, characterized in that: The density of acid addition in the internal formation process is 1.255g / ml; a two-stage formation current is adopted, the first stage current is 0.07C, the time is 1 hour, the second stage current is 0.15C, the time is 17h, and the formation capacity is 2.5 times the theoretical capacity.
9. A lead-lithium battery, characterized in that: The method is prepared by any one of claims 1 to 8.
Citation Information
Patent Citations
Lead crystal accumulator
CN101369673A
Process for manufacturing lead-acid battery grid
CN101924218A
Long-acting large-capacity lead-bearing lithium battery
CN102064306A
Container formation process for lead acid storage battery
CN102244301A
Inner forming process of tubular lead-acid storage battery
CN102347516A
